Ex vivo culturing of stromal cells with dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles promotes ectopic bone formation - Oliveira, Joaquim M. (2010)
Recently, our group has proposed a combinatorial strategy in tissue engineering principles employing carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles (CMCht/PAMAM) towards the intracellular release and regimented supply of dexamethasone (Dex) aimed at controlling stem cell osteogenic differentiation in the absence of typical osteogenic inducers, in vivo. In this work, we have investigated if the Dex-loaded CMCht/PAMAM dendrimer nanoparticles could play a crucial role in the regulation of osteogenesis, in vivo. Macroporous hydroxyapatite (HA) scaffolds were seeded with rat bone marrow stromal cells (RBMSCs), whose cells were expanded in MEM medium supplemented with 0.01 mg ml−1 Dexloaded CMCht/PAMAM dendrimer nanoparticles and implanted subcutaneously on the back of rats for 2 and 4 weeks. HA porous ceramics without RBMSCs and RBMSCs/HA scaffold constructs seeded with cells expanded in the presence and absence of 10−8 M Dex were used as controls. The effect of initial cell number seeded in the HA scaffolds on the bone-forming ability of the constructs was also investigated. Qualitative and quantitative new bone formation was evaluated in a non-destructive manner using micro-computed tomography analyses of the explants. Haematoxylin and Eosin stained implant sections were also used for the histomorphometrical analysis. Toluidine blue staining was carried out to investigate the synthesis of proteoglycan extracellular matrix. In addition, alkaline phosphatase and osteocalcin levels in the explants were also quanti!ed, since these markers denote osteogenic differentiation. At 4 weeks post-implantation results have shown that the novel Dex-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles may be bene!cial as an intracellular nanocarrier, supplying Dex in a regimented manner and promoting superior ectopic de novo bone formation.